2018
DOI: 10.3389/fimmu.2018.02183
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Pathways of Bradykinin Formation in Whole Blood From Healthy Volunteers and Patients With Hereditary Angioedema Due to C1 Inhibitor Deficiency

Abstract: Multiple pathways have been proposed to generate bradykinin (BK)-related peptides from blood. We applied various forms of activation to fresh blood obtained from 10 healthy subjects or 10 patients with hereditary angioedema (HAE-1 or −2 only) to investigate kinin formation. An enzyme immunoassay for BK was applied to extracts of citrated blood incubated at 37°C under gentle agitation for 0–2 h in the presence of activators and/or inhibitory agents. Biologically active kinins in extracts were corroborated by c-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 58 publications
6
34
1
Order By: Relevance
“…It offers a different point of view because this incriminated vasoactive mediator is short-lived and will accumulate only if its formation rate exceeds that of its breakdown. No significant spontaneous release of kinin was previously seen in whole blood or plasma sampled during remission from HAE-C1-INH patients upon incubation at 37°C but in vitro activation of fibrinolysis induced in these patients an earlier and brisker production of BK than that seen in normal controls ( 20 , 21 ). The formation of immunoreactive BK (that includes Lys-BK) induced by contact system activation or by recombinant tissue kallikrein (KLK-1) did not differ between the 2 groups.…”
Section: Introductionmentioning
confidence: 66%
See 4 more Smart Citations
“…It offers a different point of view because this incriminated vasoactive mediator is short-lived and will accumulate only if its formation rate exceeds that of its breakdown. No significant spontaneous release of kinin was previously seen in whole blood or plasma sampled during remission from HAE-C1-INH patients upon incubation at 37°C but in vitro activation of fibrinolysis induced in these patients an earlier and brisker production of BK than that seen in normal controls ( 20 , 21 ). The formation of immunoreactive BK (that includes Lys-BK) induced by contact system activation or by recombinant tissue kallikrein (KLK-1) did not differ between the 2 groups.…”
Section: Introductionmentioning
confidence: 66%
“…We previously reported that iBK formation was negligible in either whole blood or plasma incubated at 37°C without stimulus both in healthy donors and HAE patients sampled during remission (HAE-C1-INH type I or II) ( 20 , 21 ). This may be paradoxical because HK is spontaneously and progressively cleaved in the blood of patients with HAE-C1-INH ( 15 , 16 ) or HAE-nC1-INH ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations